Recent Chemotherapy Reduces the Sensitivity of [18F]Fluorodeoxyglucose Positron Emission Tomography in the Detection of Colorectal Metastases - Timothy Akhurst; Tara J. Kates; Madhu Mazumdar; Henry Yeung; Elyn Riedel; Bryan M. Burt; Leslie H. Blumgart; William R. Jarnagin; Steven M. Larson; Yuman Fong (2005)
[18F]2-fluoro-2-deoxyglucose (FDG) -positron emission tomography (PET) has become a useful tool in the assessment of patients with colorectal cancer. Patients often undergo chemotherapy as treatment for primary or metastatic colorectal malignancy. Because cytotoxic chemotherapy may decrease the cellular metabolic activity of tumor, we assessed the effects of chemotherapy on PET imaging.This is a prospective study examining detection of hepatic colorectal metastases by FDG-PET as related to use of chemotherapy. Pathologic analysis of the liver resection specimens was used as gold standard.There was significantly decreased tumor FDG uptake (as measured by the maximal standardized uptake value) in patients treated preoperatively with chemotherapy, resulting in less efficient detection of cancerous lesions. One biologic basis of this change in accuracy of PET was a significant decrease in the activity of the key glycolytic enzyme hexokinase in tumors from patients treated with chemotherapy.These results indicate that FDG-PET scanning should be interpreted in the context of concurrent cytotoxic therapy. FDG-PET scanning results may also be useful in assessment of response to such cytotoxic therapies.